The influence of the COVID-19 pandemic on work connectivity behavior - Liu, Yingyan; Zhang, Zaisheng; Zhao, Heng; Liu, Li (Frontiers in Psychology, 2023)
Introduction Based on event system theory, this study analyzed the influence of the event strength of major public health outside the organization on work connectivity behavior. Methods The study collected data from 532 employees on their psychological status and working style during the COVID-19 pandemic through an online questionnaire survey. Results The results show that driven by financial risk perception, female employees are more willing to pay work connectivity behavior than male employees and unmarried employees are more willing to pay work connectivity behavior than married employees. The risk perception of employees aged 28–33 has the greatest impact on workplace behavior. The impact of financial risk perception on behavior of employees without children is much higher than that of employees with children. The influence of financial risk perception and social risk perception on their behavior of employees with master’s degree is much higher than that of health risk perception, but the workplace behavior of employees with doctor’s degree is mainly affected by health risk perception. Discussion The novelty of the Corona Virus Disease event has a negative influence on work connectivity duration. The criticality, disruption of the Corona Virus Disease event has a positive influence on work connectivity duration. The criticality of the Corona Virus Disease event has a positive influence on work connectivity frequency. Employees’ social risk perception, financial risk perception and health risk perception has a positive influence on the work connectivity duration and work connectivity frequency.